PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP LOYALITAS KARYAWAN PADA PT PELABUHAN INDONESIA (PERSERO) REGIONAL 1 CABANG DUMAI - Anggun Putri Wel Sofia; Seno Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research is motivated by the importance of human resource management in the progress of a company. To increase employee loyalty, the company needs to manage the human resources in it. This research was conducted at PT Pelabuhan Indonesia (Persero) Regional 1 Dumai Branch, located at Jl Sultan Syarif Kasim No.1 Tlk Binjai Dumai. The purpose of this study was to determine the effect of work environment and work motivation on employee loyalty at PT Pelabuhan Indonesia (Persero) Regional 1 Dumai Branch. Work environment and work motivation as variables X1 and X2 and employee loyalty as variable Y. The research method used is descriptive and quantitative analysis methods obtained from the results of the questionnaire and measured using a Likert scale technique. The data is then processed using the SPSS program. This study also uses the method of simple linear regression analysis and multiple linear regression analysis. The sample in this study was 62 respondents from the total population using the total sampling method. The results showed that testing the first hypothesis, namely the work environment has a positive effect on employee loyalty. The second test, work motivation has a positive effect on employee loyalty. The results of the F-test show that the work environment and work motivation simultaneously have a positive effect on employee loyalty. Keywords: Work Environment, Work Motivation, Employee Loyalty